An Interdisciplinary Perspective Of Mental Health Problems : A Review - Alamsyah, Dani (Journal of Literature Language and Academic Studies, 2023)
Mental health is a multifaceted phenomenon that has garnered increasing attention in recent years. This paper provides an interdisciplinary perspective on mental health, drawing from fields such as psychology, sociology, and public health. Through a comprehensive literature review, we explore the complex nature of mental health, including its definition, measurement, and the factors that contribute to mental illness. We also examine the impact of social and cultural factors on mental health, as well as the role of stigma and discrimination in perpetuating mental health disparities. The paper concludes by highlighting the importance of a holistic approach to mental health that addresses the individual, social, and systemic factors that influence mental well-being. The paper begins by exploring the definition of mental health and the various frameworks used to conceptualize it. We then delve into the measurement of mental health, including the use of standardized assessments and self-report measures. We also explore the factors that contribute to mental illness, including genetic and environmental factors, as well as the interaction between the two